Ultrasound Targeted Microbubble Destruction-Mediated Delivery of a Transcription Factor Decoy Inhibits STAT3 Signaling and Tumor Growth - Kopechek, Jonathan A. (Theranostics, 2015)
Signal transducer and activator of transcription 3 (STAT3) is constitutively activated in many cancers where it acts to promote tumor progression. A STAT3-specific transcription factor decoy has been developed to suppress STAT3 downstream signaling, but a delivery strategy is needed to improve clinical translation. Ultrasound-targeted microbubble destruction (UTMD) has been shown to enhance image-guided local delivery of molecular therapeutics to a target site. The objective of this study was to deliver STAT3 decoy to squamous cell carcinoma (SCC) tumors using UTMD to disrupt STAT3 signaling and inhibit tumor growth. Studies performed demonstrated that UTMD treatment with STAT3 decoy-loaded microbubbles inhibited STAT3 signaling in SCC cells in vitro. Studies performed in vivo demonstrated that UTMD treatment with STAT3 decoy-loaded microbubbles induced significant tumor growth inhibition (31-51% reduced tumor volume vs. controls, p < 0.05) in mice bearing SCC tumors. Furthermore, expression of STAT3 downstream target genes (Bcl-xL and cyclin D1) was significantly reduced (34-39%, p < 0.05) in tumors receiving UTMD treatment with STAT3 decoy-loaded microbubbles compared to controls. In addition, the quantity of radiolabeled STAT3 decoy detected in tumors eight hours after treatment was significantly higher with UTMD treatment compared to controls (70-150%, p < 0.05). This study demonstrates that UTMD can increase delivery of a transcription factor decoy to tumors in vivo and that the decoy can inhibit STAT3 signaling and tumor growth. These results suggest that UTMD treatment holds potential for clinical use to increase the concentration of a transcription factor signaling inhibitor in the tumor.